MENINGKATKAN HASIL BELAJAR SISWA MELALUI KURIKULUM MERDEKA DENGAN MENGGUNAKAN MODUL PEMBELAJARAN KELAS VII DI MTS TERPADU DARUN NAJAH KEDIRI - Sugianti, Wiwis; Arifin, Zainal; Irmayanti, Elis (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2024)
Education is an effort to realize and develop student potential. Education in Indonesia has undergone several curriculum changes with the aim of improvement. The advantage of the Merdeka Curriculum is that learning is much more active and creative. Therefore, the Merdeka Curriculum is widely implemented in schools, including the Darun Najah Kediri Integrated MTs. Based on initial observations made, it is known that the teacher has used the Independent Curriculum. Even though there are many positive impacts, implementing the Independent Curriculum still has several shortcomings, such as many students not understanding the Independent Curriculum. Hence, students are less active in participating in learning at school, which also decreases student learning outcomes. This research aims to determine whether implementing the Merdeka Curriculum learning module can improve the learning outcomes of class VII students at MTS Terpadu Darun Najah Kediri. This research uses the Classroom Action Research (PTK) method with social studies subject material on the Geographical Location of Indonesia. The research results show an increase in student learning outcomes, as indicated by an increase in students who get scores above the KKM. The percentage of students who scored above the KKM from the pre-cycle was 13.33%, 20% for the first cycle, 30% for the second cycle, and 60% for the third cycle.